Report of farmer learning visits to model farms in Wakiso and Mukono districts, Uganda - Oba, Peter; Businge, Martha; Hasahya, Emmanuel; Kyobe, Francis; Kawuma, Peter; Ssimbwa, David; Happy, Noeline; Marunga, Caroline; Kaweesa, Peter; Wairagala, Pamela; Ahumuza, Ronnie; Dione, Michel M.; et al. (International Livestock Research Institute, 2024)
The International Livestock Research Institute (ILRI), working in collaboration with district local governments in Uganda's Central Region and other national partners, is implementing the CGIAR Initiative on Sustainable Animal Productivity for Livelihoods, Nutrition and Gender inclusion (SAPLING) to address health and other productivity constraints identified in the pig value chain. SAPLING’s primary objective is to enhance livestock productivity, income generation, and sustainability among women, men, and youth smallholder farmers in Uganda. Pig farming plays a crucial role in the livelihoods of especially rural communities in Uganda, contributing significantly to both food security and income generation. However, significant barriers remain to improved pig production and productivity in Uganda. Following the co-creation workshops held in Mukono, Wakiso, Mpigi and Masaka districts in September 2022 with key stakeholders (pig farmers, district veterinary officers and animal health care workers, and academia), pig health, management practices, and diseases were identified as significant barriers to realizing the full potential of the pig sector in the country.